2020
DOI: 10.1042/bsr20201519
|View full text |Cite
|
Sign up to set email alerts
|

Plasma lipidomic analysis of sphingolipids in patients with large artery atherosclerosis cerebrovascular disease and cerebral small vessel disease

Abstract: Background Sphingolipids mainly consist of ceramides(Cer), sphingomyelins(SM) and glycosphingolipids. Sphingolipids are related with coronary heart disease and metabolic disease, but there’re few studies about cerebrovascular disease. The purpose was to detect sphingolipids in plasma of patients with large artery atherosclerosis (LAA) cerebrovascular disease and cerebral small vessel disease (CSVD) to explore the similarities and differences of pathogenesis of the two subtypes. Methods 20 patients with LAA cer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
1
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 43 publications
1
11
1
4
Order By: Relevance
“…Previous metabolomics studies have shown associations of lower levels of ceramide ratios with fewer number of cerebral microbleeds 20 and increased risk of incident dementia, 21 and another study showed associations of ceramides and sphingomyelins with SVD. 22 In the present study, lower levels of serum sphingomyelins and ceramides were associated with lower MDNPH, higher WMH volume and PSMD, increased number of lacunes, greater brain atrophy and impaired cognition in baseline analyses even after further adjustment. Only one sphingomyelin had a statistically significant association with executive function when assessing the annualized change in metabolite levels, suggesting that the absolute levels of the metabolites at baseline are more relevant in evaluating their effects on SVD and cognition than how those levels change over time.…”
Section: Discussionsupporting
confidence: 47%
“…Previous metabolomics studies have shown associations of lower levels of ceramide ratios with fewer number of cerebral microbleeds 20 and increased risk of incident dementia, 21 and another study showed associations of ceramides and sphingomyelins with SVD. 22 In the present study, lower levels of serum sphingomyelins and ceramides were associated with lower MDNPH, higher WMH volume and PSMD, increased number of lacunes, greater brain atrophy and impaired cognition in baseline analyses even after further adjustment. Only one sphingomyelin had a statistically significant association with executive function when assessing the annualized change in metabolite levels, suggesting that the absolute levels of the metabolites at baseline are more relevant in evaluating their effects on SVD and cognition than how those levels change over time.…”
Section: Discussionsupporting
confidence: 47%
“…Furthermore, high levels of long-chain Cer have been associated with BBB disruption ( Vutukuri et al, 2018 ; Bekhite et al, 2021 ). Moreover, elevated plasma levels of Cer were recently observed from stroke patients with large artery atherosclerosis, and cerebral small vessel disease ( You et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…ACC1, mainly acting on the fatty acid synthesis and fatty acid oxidation, is observed to involve in metabolic syndrome (including atherogenic dyslipidemia, diabetes, and hypertension), which is a clustering of cardiovascular/cerebrovascular risk factors. [21][22][23][24] For instance, one previous study shows that the overexpression of ACC1 facilitates lipid accumulation in macrophage foam cells and further aggravates atherosclerosis in apolipoprotein E-deficient mice. 25 Also, another study finds that ACC1 expression is elevated in atherosclerotic mice.…”
Section: Discussionmentioning
confidence: 99%